Cost effectiveness of a multi-component school-based physical activity intervention targeting adolescents: the ‘Physical Activity 4 Everyone’ cluster randomized trial - Sutherland, Rachel (Int J Behav Nutr Phys Act, 2016)
BACKGROUND: Few school-based interventions have been successful in reducing physical activity decline and preventing overweight and obesity in adolescent populations. As a result, few cost effectiveness analyses have been reported. The aim of this paper is to report the cost and cost effectiveness of the Physical Activity 4 Everyone (PA4E1) intervention which was a multi-component intervention implemented in secondary schools located in low-income communities. Cost effectiveness was assessed using both the physical activity and weight status trial outcomes. METHODS: Intervention and Study Design: The PA4E1 cluster randomised controlled trial was implemented in 10 Australian secondary schools (5 intervention: 5 control) and consisted of intervention schools receiving seven physical activity promotion strategies and six additional strategies that supported school implementation of the intervention components. Costs associated with physical activity strategies, and intervention implementation strategies within the five intervention schools were estimated and compared to the costs of usual physical activity practices of schools in the control group. The total cost of implementing the intervention was estimated from a societal perspective, based on the number of enrolled students in the target grade at the start of the intervention (Grade 7, n = 837). Economic Outcomes: The economic analysis outcomes were cost and incremental cost effectiveness ratios for the following: minutes of moderate-to-vigorous physical activity (MVPA) per day gained, MET hours gained per person/day; Body Mass Index (BMI) unit avoided; and 10 % reduction in BMI z-score. RESULTS: The intervention cost AUD $329,952 over 24 months, or AUD$394 per student in the intervention group. This resulted in a cost effectiveness ratio of AUD$56 ($35–$147) per additional minute of MVPA, AUD$1 ($0.6–$2.7) per MET hour gained per person per day, AUD$1408 ($788–$6,570) per BMI unit avoided, and AUD$563 ($282–$3,942) per 10 % reduction in BMI z-score. CONCLUSION: PA4E1 is a cost effective intervention for increasing the physical activity levels and reducing unhealthy weight gain in adolescence, a period in which physical activity typically declines. Additional modelling could explore the potential economic impact of the intervention on morbidity and mortality. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12612000382875.